Epigenetic programming of pediatric high-grade glioma: Pushing beyond proof of concept to clinical benefit - Groves, Andrew; Cooney, Tabitha M. (Frontiers in Cell and Developmental Biology, 2022)
Pediatric high-grade gliomas (pHGG) are a molecularly diverse group of malignancies, each incredibly aggressive and in dire need of treatment advancements. Genomic analysis has revolutionized our understanding of these tumors, identifying biologically relevant subgroups with differing canonical mutational profiles that vary based on tumor location and age. In particular, the discovery of recurrent histone H3 mutations (H3K27M in diffuse midline glioma, H3G34R/V in hemispheric pHGG) as unique “oncohistone” drivers revealed epigenetic dysregulation as a hallmark of pHGG oncogenesis. While reversing this signature through epigenetic programming has proven effective in several pre-clinical survival models, early results from pHGG clinical trials suggest that epigenetic modifier monotherapy will likely not provide long-term disease control. In this review we summarize the genetic, epigenetic, and cellular heterogeneity of pHGG, and highlight potential paths forward for epigenetic programming in this devastating disease.